The Effect of Feeding Maggot Flour Hermetia illucens at Different Doses on Absolute Weight Growth of Dumbo Catfish Clarias gariepinus L Size 3 - 4 Cm - Nur Muhammad Fatih Asror Al Murtadho; Nurul Hayati; Muhajir Muhajir (CV. AFDIFAL MAJU BERKAH, 2026)
Based on statistical data from the Directorate General of Aquaculture, catfish production has shown an increase every year, with 990,000 tons in 2020, 1 million tons in 2021, 1.1 million tons in 2022, and 1.2 million tons in 2023. One of the alternative raw materials recommended by the Directorate General of Aquaculture to replace fish meal is maggot. This study aims to determine the effect of feeding maggot meal (Hermetia illucens) at different doses on the absolute weight growth of Dumbo catfish (Clarias gariepinus) measuring 3 – 4 cm. The benefits of this study are expected to serve as a source of knowledge and information, particularly for researchers and generally for the wider community, regarding the effects of feeding maggot meal (Hermetia illucens) at different doses on the absolute weight growth and absolute length growth of Dumbo catfish (Clarias gariepinus) measuring 3 – 4 cm. The research method was designed using a Completely Randomized Design (CRD) with four treatments, each consisting of six replications, resulting in 24 experimental units. The treatments were as follows P1: dose 100%, P2: dose 75%, P3: dose 50% and P4: dose 25%. The data from the research were analyzed using Analysis of Variance (ANOVA) and followed by the Least Significant Difference (LSD) test. The results showed that the best absolute weight growth of Dumbo catfish was observed in the P4 treatment dose 25%, with an average of 1.95 g. Water quality during the study was optimal, with temperatures ranging from 27.1°C to 29.4°C and pH levels ranging from 7.3 to 8.1.